EVALUASI KINERJA BAN HD 785-7 DAN 777 PADA JALAN ANGKUT TAMBANG DARI FRONT 2 KE CRUSHER III A DAN III B PENAMBANGAN BATU KAPUR PT. SEMEN PADANG - Indra Lesmana Putra; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. PT. Semen Padang is one of the companies engaged in limestone mining located in Bukit Karang Putih, Indarung, Padang City. Each transport activity requires a mechanical device as a means to facilitated transport activities. PT. Semen Padang uses dump trucks Komatsu HD 785-7 and Caterpillar 777 D to move material from loading point to the Crusher. One of the important component of dump truck in transportation activities is the tires. Tires are one of the important components because the tires are in direct contact with the road surface. The main function of the tires is to hold the weight of a vehicle and the charge that is tangent to the ground surface, controlling the running of the vehicle and continue the power from the engine. So that the selection of proper tires becomes an important factor for the operation to run smoothly. To minimize the risk of tire damage, it is necessary to evaluate the performance of tires by conducting analysis of Key Performance Indicator (KPI) parameters. Which are used to measure tire performance are Ton Kilometer Per Hour (TKPH), Tread Utilization Rated (TUR), Lifetime, and transport condition. If the actual TKPH value has exceeded the TKPH rating, then the lifetime of the tires is not optimum , because it has passed the tire endurance limit. For the percentage value of the actual tire tread level (TUR), all tire used in the dump truck unit at the location must have a TUR safety standard of 85%.Keywords: Tires, Dump Trucks, KPI, TKPH, TUR, Lifetime.